Peran zakat dalam mewujudkan hifdzul mal: perspektif maqasid syariah - Kirana, Ayu Cendana (Maliki Interdisciplinary Journal, 2025)
Maqasid al-Shari'ah, which aims to achieve benefits and prevent harm, includes a key element, namely hifdzul mal or the preservation of wealth. Zakat, as one of the main instruments in Islam, plays a vital role in achieving this goal by purifying wealth, strengthening social solidarity, and creating a more equitable distribution of wealth. Zakat not only functions as an individual act of worship but also as an economic empowerment tool through efficient management and distribution. This study uses a descriptive-analytical method with a literature review approach to explore the role of zakat in economic empowerment and wealth management in the Muslim community. The findings of the study show that zakat has great potential in reducing poverty, addressing social inequality, and creating prosperity for the Muslim community. However, the optimalization of zakat still faces challenges related to suboptimal management and low public awareness. Therefore, it is important to ensure alignment between the principles of maqasid syariah and the management of zakat institutions to achieve greater social and spiritual benefits for the Muslim community.